He hokinga ki te mauri: strengthening te Tiriti o Waitangi public health education in tertiary education settings. Issue 8 (16th November 2020) - Came, H.A.; Warbrick, I.; Doole, C.; Hotere-Barnes, A.; Sessa, M.
ABSTRACT: Te Tiriti o Waitangi [te Tiriti] articulates the relationship between the government and Māori [Indigenous New Zealanders]. Universities have a responsibility to prepare graduates to work with te Tiriti. The literature on teaching te Tiriti is sparse. In this conceptual paper, we propose he hokinga ki te mauri [a return to vibrancy] as a framework for teaching te Tiriti. First, te upoko involves using intellectual rationale and covering core te Tiriti curriculum related to issues such as He Whakaputanga [the Declaration of Independence] and the texts of te Tiriti. Second, it offers strategies for te ngākau – involving heart and wairua [spirit]. Finally, ngā ringa – involves practical application. The authors maintain this novel approach supports teachers to depart from the weighty requirements of advanced technical expertise, providing flexibility to scaffold curriculum. Across the world, working with the ongoing impacts of colonisation gives rise to a range of politically and emotionally charged topics, we hope that our method might strengthen the teaching and learning associated with decolonisation.